Fanzines como instrumento de expressão atrás das grades: processos educativos através da arte - Frasson, Tamires Fernanda Baptista (Universidade Federal de São Carlos, 2024)
In thinking about possibilities for dialogic learning inside spaces of restriction and deprivation of liberty, the proposal of this paper focuses on a pedagogical action that can promote autonomy for people in this situation: the production of fanzines. This theme was chosen due to the combination of Arts and Language. Therefore, the purposes of this research are: to investigate the educational processes that emerge from the production of fanzines during learning workshops held with students in a space of restriction and deprivation of liberty; analyze fanzines as a pedagogical resource used in school and non-school activities and explore ways to apply it; identify how fanzines can provide moments of self-expression and contribute to the process of humanization of the workshop participants; evaluate the creations made in the workshops and, based on them, promote a meaningful learning for the incarcerated students. Thus, bibliographical research was used in the first stage, conducting a systematic review of the topic. Considering that the stance adopted for this study is grounded on Paulo Freire’s principles, which means, humanizing and liberating, in order to answer the questioning raised by the research, it was exercised in the fieldwork the interaction and relationship of proximity between the researcher and the participants, based on affectivity and dialogue. That way, as a second stage, an action research was carried out with learning workshops at the resocialization center located in Jaú, São Paulo, during Art lessons with two multi graded classes of middle school. From the development of the workshops, it was possible to obtain data on the educational processes emerging from art, such as: autonomy, development of self confidence and trust in others, dialogicity, attention, interest, dedication, motivation, frustration, respect for differences and creativity. Furthermore, the research presents the potential for expression, humanization and the promotion of learning behind bars through fanzine productions. In this research we also found that there are few works on fanzines in these spaces. Therefore, we consider that it is necessary to give more importance to the topic, as it proved to be relevant in its results. We hope that this work will be read not only by people in the academic field. But, mainly, that it reaches people who are deprived of their freedom, inspiring them and showing them new paths through art.
Fanzines as an instrument of expression behind bars: educational processes through art
Keywords: Processos educativos; Fanzines; Prática social; Espaços de restrição e privação de liberdade; Educational processes; Social practice; Spaces of restriction and deprivation of liberty; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM